Detection of the Helicobacter pylori caga gene in gastric biopsies from dyspeptic patients using PCR method in Mataram General Hospital - Soewignyo Soemodihardjo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2000)
A polymerase chain reaction assay (PCR) for the diagnosis of Helicobacter pylori in human gastric biopsies from 44 dyspeptic patients was developed. From endoscopic diagnosis, the sample consisted of 4 patients with gastric cancer, 4 patients with duodenal ulcer, 3 patients with ventricular ulcer, 3 patients with both ventricular ulcer and duodenal ulcer and 31 patients with chronic gastritis. The H. pylori infection was diagnosed using nested PCR, which consisted of two primers of the urease gene fragment. From 44 specimens with urease positive, 39 specimens were positive for cagA strain (88,6%). This reflects a very high frequency of the cagA gene in the Helicobacter pylori infection. The meaning of this is still unclear. There was no significant difference in the cagA status of ulcer dyspeptic patient and non- ulcer dyspeptic patients.  Key words: CagA gene, Helicobacter pylori, PCR